Exploring differences in leadership styles between men and women school principals - Mouchantaf, Maha S (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2005)
The purpose of the present study was to examine differences in leadership styles between men and women school principals in Lebanon. In other words, thi s study explored gender differences among school principals. The sample of thi s study consisted of two principals and twelve teachers belonging to two schools in Lebanon. The instruments used were interviews and observation sessions developed accord ing to the western literature. The results reveal ed that women school principals lead in a more open, efficient and democratic way than men school principals do. The male school principal in this study was authoritarian, used one way communication patterns, took decisions unilaterally, didn't empower the teachers and handled conflicts in a one-sided approach. On the other hand, the female school principal in this study was democratic, used direct interpersonal contacts, decided collaboratively, empowered her teachers and consequently trusted them and resolved confl icts justly. Similarly, the teachers under the male school principal perceived him as authoritarian and the teachers under the female school principal described her as democrati c. Additionally, the observation reports suppOlted the results and reveal ed the existence of two different leadership styles in the two schools.
: Mémoire
Keywords: Gender; Gestion scolaire; School management; Sexe